2013
DOI: 10.4103/0974-777x.116872
|View full text |Cite
|
Sign up to set email alerts
|

HIV-2 infection: Where are we today?

Abstract: Context:The choice of antiretroviral therapy for HIV-2 differs from that for HIV-1, underscoring the importance of differentiating between the two.Aims:The current study was planned to find out the prevalence of HIV-2 infection at our center and to find out the utility of the current diagnostic algorithm in identifying the type of HIV infection.Setting and Design:Retrospective analysis in a tertiary care teaching institute over a period of three years.Materials and Methods:All patients diagnosed as HIV infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, our findings for those who were dual infected was 1.4% which is similar to Tadokar and Kavathekar[9] study findings, but again studies have shown a range from 0% to 1.65%. [67891011] Our findings in relation to the prevalence of HIV-1, HIV-2, and dual infection of HIV-1 and 2 among HIV-infected individuals when compared to other studies are summarized in Table 3. These findings suggest that HIV-2 and dual infections are prevalent in and around Mangalore.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, our findings for those who were dual infected was 1.4% which is similar to Tadokar and Kavathekar[9] study findings, but again studies have shown a range from 0% to 1.65%. [67891011] Our findings in relation to the prevalence of HIV-1, HIV-2, and dual infection of HIV-1 and 2 among HIV-infected individuals when compared to other studies are summarized in Table 3. These findings suggest that HIV-2 and dual infections are prevalent in and around Mangalore.…”
Section: Discussionmentioning
confidence: 76%
“…[1] It is well documented that HIV-1 infection is predominantly found, but HIV-2 infection has also been detected occasionally now and then. [67891011] The data in relation to the seroprevalence rate of HIV-2 among HIV-infected individuals is lacking from in and around Mangalore; hence, this study was conducted with the main objective to determine the seroprevalence and analyze the sociodemographic pattern, clinical and laboratory features of these infected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the highest prevalence was reported in Guinea-Bissau, including around 8% of the adult population and up to 20% in the subgroup of individuals over the age of 40 [16]. At the turn of the 20th and 21st centuries, other West African countries significantly affected by HIV-2 were Senegal, Niger, Burkina Faso, Ghana, Guinea, Benin, Liberia, Togo, Angola, Mozambique, and São Tomé (all with a prevalence of >1%) [10,15,17,18]. In the same geographical area, between 10 and 20% of HIV infections included HIV-2 with doubly infected or reactive HIV-1/HIV-2 individuals [19].…”
Section: Hiv-2 Origin and Infection Worldwidementioning
confidence: 99%
“…3,4 Sexual transmission is responsible for the majority of HIV-2 infections due to infected semen or cervico-vaginal secretions containing infected lymphocytes. 5 Ideally, a vaginal/rectal microbicide should have the following features: to be acceptable and affordable, offer maximal and immediate protection, remain in the vagina for a few hours to act against the sexual transmitted diseases (STDs) during and after sexual intercourse, not leak immediately after application, not accumulate to avoid toxicity effects, not affect the normal vaginal flora, and be compatible with male latex condom. [6][7][8] Dendrimers are a class of well-defined hyper-branched polymers with a nanoscale globular shape, well-defined functional groups at the periphery, hydrophobic/hydrophilic cavities in the interior and low polydispersity.…”
Section: Human Immunodeficiency Virus (Hiv) and Other Sexually Transmmentioning
confidence: 99%